1993
DOI: 10.1246/bcsj.66.2033
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structures, and Properties of 2,3,6,7-Tetrathiabenzo[1,3-cd:4,6-cd′]dipentalene and Its Methyl, Ethyl, Methylthio, and Ethylthio Derivatives: Novel Fused Polynuclear Heteroarenes

Abstract: The title heteroarene (TBD) isoelectronic with perylene was synthesized by way of a dimerization of thieno[2,3-b]thiophene. In addition, 1,4,5,8-tetramethyl, tetraethyl, tetrakis (methylthio), and tetrakis (ethylthio) derivatives were readily obtained from TBD. An X-ray crystallographic analysis of TBD demonstrated that the molecular structure is quite planar and symmetrical, but strained in the bond angles. The crystal structure comprises herringbone-type column stacking with intercolumnar heteroatomic intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…[80][81][82] For example, Otsubu and co-workers reported an elegant synthesis by the lithiation of 1-trimethylsilylpentadiyne with n-BuLi/t-BuOK, followed by trapping of the resultant anion with carbon disulfide. [81] Ring closure upon work-up afforded 2-trimethylsilylthieno [2,3-b]thiophene, which could readily be desilylated by treatment with tetrabutylammonium fluoride to afford thieno [2,3-b]thiophene. [82] For larger scale preparations, a more convenient route was developed from commercially available 2-thiophenethiol (Scheme 1).…”
Section: Thienothiophene Monomer Preparationmentioning
confidence: 99%
“…[80][81][82] For example, Otsubu and co-workers reported an elegant synthesis by the lithiation of 1-trimethylsilylpentadiyne with n-BuLi/t-BuOK, followed by trapping of the resultant anion with carbon disulfide. [81] Ring closure upon work-up afforded 2-trimethylsilylthieno [2,3-b]thiophene, which could readily be desilylated by treatment with tetrabutylammonium fluoride to afford thieno [2,3-b]thiophene. [82] For larger scale preparations, a more convenient route was developed from commercially available 2-thiophenethiol (Scheme 1).…”
Section: Thienothiophene Monomer Preparationmentioning
confidence: 99%
“…11 The C-C bond common to both the chelate and the thiophene rings, have similar distances for 7, 13 and 15 (Table 2).…”
Section: Structural Studies Of the Carbene Complexesmentioning
confidence: 97%
“…However, the synthesis of 4,4′-dibromothieno[2,3-b]thiophene requires the initial formation of 4,4′,5,5′-tetrabromothieno[2,3-b]thiophene, followed by the debromination of the 5-and 5′-positions. 11,15 Thus, as the thiophene results indicated that it was possible to obtain both mono-and bischelated carbene complexes from the tetrabromothiophene precursor, 4,4′,5,5′-tetrabromothieno [2,3-b]thiophene was chosen as substrate to target the formation of both classes of chelated complexes (10, 11, 14 and 15). The reaction of 4,4′,5,5′-tetrabromothieno[2,3-b]thiophene with 2.4 equivalents of n-BuLi, 2 equivalents of metal carbonyl and another addition of 2.4 equivalents n-BuLi, afforded a number of carbene complexes.…”
Section: Alkylation With Excess [Et 3 O][bfmentioning
confidence: 99%
See 1 more Smart Citation
“…-The development of new strategies for the syntheses of polycondensed thiophenes has recently received much attention because of the unusual aromatic [I] and photophysical [2] properties displayed by these compounds as well as the potential for use of these derivatives as organic conductors and superconductors [3], electron acceptors [4] and donors [5], photosensitive receptors [6], and as materials for nonlinear optics [7]. -The development of new strategies for the syntheses of polycondensed thiophenes has recently received much attention because of the unusual aromatic [I] and photophysical [2] properties displayed by these compounds as well as the potential for use of these derivatives as organic conductors and superconductors [3], electron acceptors [4] and donors [5], photosensitive receptors [6], and as materials for nonlinear optics [7].…”
mentioning
confidence: 99%